Calculation of the Lost Profit in Business Damage Cases - Barbora Nohýnková (European Financial and Accounting Journal, 2022)
This article deals with the method of calculating lost profits, or determining the relevant basic formula, respectively. The aim is to summarise the knowledge about the used calculations, evaluate them and comment on the possibility of their use with regard to the purpose of the prepared calculation of economic damage and the nature of the economic damage case, respectively. The link of the area of quantification of economic damages with a certain legislative framework naturally follows from the very subject of the economic research, i.e. damage. I will examine the above within the legislation of the Czech Republic, which uses different terms related to economic damage and which represent different levels/categories of damage. Based on a search of the relevant literature and the case law, the intention of this article is to determine which parts of the calculation represent the levels/categories of damages that may be caused and the impact of this categorisation on the appraiser's overall approach to the quantification of appropriate damages and the complexity of proving.
Keywords: G30; 650; Economic damage; Actual damage; Lost profits; Level of the damage; Category of the damage; Formula